Bacterial Contamination in the Components of the Chickens' Eggs: S. A. Abed, S.M. Heeder , Z.G.Mohammed - Abed, S. A. (The Iraqi Journal of Veterinary Medicine, 2020)
In 120 hen eggs ( local eggs , hatching eggs and table eggs ) a bacteriologicalpollution with high rate was observed by isolating 427 bacterial isolates fromwhich 199 isolates related to the egg's shell , 117 isolates related to albumen sac,and 111 isolates related to yolk sac .The Salmonella ssp isolates were the greater number (142 isolates) ,Echerichia coli ( 138 isolates ) , Streptococcus ssp ( 89 isolated) and latelyStaphylococcus ssp ( 58 isolates ) which was never isolated from internal eggcomponents (Albumen Sac and yolk sac) .The study explains that the shell of the egg is more contaminated thanAlbumen Sac and yolk sac and that the table egg is more contaminated than theother groups.